Howell‐Jolly bodies on peripheral smear leading to the diagnosis of congenital hyposplenism in a patient with septic shock. Issue 8 (4th July 2015) - Mathew, Hannah; Dittus, Christopher; Malek, Anita; Negroiu, Andreea
Key Clinical Message: We present a case of isolated congenital hyposplenism that was discovered after the peripheral smear revealed Howell‐Jolly bodies. This case serves as the basis for a review of hyposplenism for the general practitioner. Abstract : We present a case of isolated congenital hyposplenism that was discovered after the peripheral smear revealed Howell‐Jolly bodies. This case serves as the basis for a review of hyposplenism for the general practitioner.